The siliciclastics/carbonates shift in the Jurassic of the Western Caucasus (central northern Neo-Tethys): reconsidering research over the last 50 years - Ruban, Dmitry A. (Geologos, 2019)
A chain of carbonate platforms evolved in the northern Neo-Tethys during the Late Jurassic, but current knowledge remains incomplete as long as data from several larger regions, such as the Western Caucasus, are not included. In order to fill this gap, it is here suggested to reconsider the information accumulated chiefly during Soviet times. Although these data are too general, they still matter with regard to some regional characteristics and tentative interpretations. Available data on the spatio-temporal distribution of Bajocian-Callovian sedimentary rocks are summarised in a novel way which permits documentation of depositional trends at six representative localities in the Western Caucasus. The extent of the carbonate platform increased at two localities since the Late Callovian and at a third since the Middle Oxfordian. Three additional sites were characterised either by non-deposition or deep-marine sedimentation. The onset of carbonate platform development marked a remarkable shift from chiefly siliciclastic to carbonate deposition, although this event was not sudden everywhere. The Bathonian pulse of tectonic activity, coupled with the eustatic sea level rise, allowed shelves to expand during the Callovian-Oxfordian, with a reduction in siliciclastic input from islands and sea-water that became well oxygenated and warmer. These conditions were conducive to biogenic carbonate production, allowing the carbonate platform to expand subsequently.